Perlindungan Konsumen Terhadap Tindakan Diskriminasi oleh Pelaku Usaha Rental Motor di Desa Canggu Badung - Ni Putu Citra Juli Artini; Ni Made Jaya Senastri; I Made Aditya Mantara Putra (Jurnal Analogi Hukum, 2024)
Canggu Village is a tourist village visited by foreign and local tourists. In this case, the community opens various business sectors in Canggu Village, one of which is the motorcycle rental business. In practice, there are motorcycle rental businesses that do not carry out their business activities based on Law Number 8 of 1999 concerning Consumer Protection regarding violations of consumer rights. The formulation of this research problem: 1) What factors cause motorcycle rental businesses to discriminate against consumers in Canggu Village, Badung? 2) How are legal protection efforts against consumers for discrimination by motorcycle rental businesses in Canggu Badung Village? Type of empirical legal research with the type of approach legislation and facts. The results showed that the factors causing motorcycle rental business actors to discriminate against consumers were irresponsible consumer actions by taking away the rented motorbike. Legal protection for consumers against discrimination by motorcycle rental businesses is preventive protection through guidance by Bendesa Adat Canggu to motorcycle rental businesses in Canggu Village and repressive protection, namely consumers who feel harmed can report to the village office by bringing evidence of discrimination by business actors that harm consumers.